2004
DOI: 10.1080/03610730490251469
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Probabilistic Learning in Single- and Multiple-Cue Tasks

Abstract: The objective of the study was to examine some of the conditions under which elderly people are able to learn probabilistic inverse relationships and when this type of learning is no longer possible. Two kind of tasks were used: (a) two single-cue learning tasks with either direct or inverse relationships (the Single-Cue Probability Learning paradigm), and (b) three two-cue learning tasks, one with two direct relationships, one with a combination of direct and inverse relationships, and one with two inverse re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
19
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 38 publications
9
19
0
2
Order By: Relevance
“…These Wndings are consistent with those of Klahr, Fay, and Dunbar (1993) and Kuhn, Schauble, and Garcia-Mila (1992) showing that at around Wfth or sixth grade, children begin to develop eVective strategies for generating and interpreting evidence in moderately complex, multivariable contexts (see also Kuhn, Amsel, & O'Loughlin, 1988). The Wndings are also consistent with those of Chasseigne et al (1997Chasseigne et al ( , 2004 showing that, as a whole, the 18-to 25-year-olds were able to acquire much task knowledge in a direct relation-inverse relation ecology.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These Wndings are consistent with those of Klahr, Fay, and Dunbar (1993) and Kuhn, Schauble, and Garcia-Mila (1992) showing that at around Wfth or sixth grade, children begin to develop eVective strategies for generating and interpreting evidence in moderately complex, multivariable contexts (see also Kuhn, Amsel, & O'Loughlin, 1988). The Wndings are also consistent with those of Chasseigne et al (1997Chasseigne et al ( , 2004 showing that, as a whole, the 18-to 25-year-olds were able to acquire much task knowledge in a direct relation-inverse relation ecology.…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, these individuals failed in the same way as did most elderly people tested in previous studies conducted on aging samples (Chasseigne et al, 1997(Chasseigne et al, , 2004Léoni, Mullet, & Chasseigne, 2002). In other words, the trouble that children experienced at learning to use an inverse relation cue in the current study parallels the trouble that elderly people (over 74 years of age) experienced at learning to use an inverse relation in structurally similar learning situations.…”
Section: Discussionsupporting
confidence: 63%
“…The results indicated that not only did the elderly score fewer points than the younger participants, but they also needed more trials to reach the learning criterion. These results fit in with behavioral data indicating that older participants are less efficient than young participants at reversal learning (Chasseigne et al, 2004;Weiler, Bellebaum, & Daum, 2008; see also Tsuchida, Kubo, & Kojima, 2002).…”
Section: Neuroeconomics and Aging: The Probability Parametersupporting
confidence: 85%
“…It also requires that a division operation needs to be applied. The present findings are consistent with functional learning studies showing that inverse relationships are much more difficult to learn than direct relationships (Brehmer 1974;Slovic 1974;Chasseigne et al 2004;Musielak et al 2006). The presence of only one inverse relationship in a task decreases the efficiency of the learning performance Chasseigne et al 2004;).…”
Section: Resultssupporting
confidence: 91%